PERBEDAAN TINGKAT KESEHATAN BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Ervita Safitri; Fildhzah Rani; Darma Yanti (Politeknik Negeri Batam, 2021)
The purpose of this study was to determine the differences in health level of conventional and Islamic commercial banks listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 study period. The application of health level is based on the RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) method determined by Bank Indonesia. The data analysis method used in this study is the independent sample t-test. The total sample of this study is 6 banks (3 conventional commercial banks and 3 Islamic commercial banks). The results showed that based on the ratio of LDR, CAR and GCG there was no differences in Health Level of conventional and Islamic commercial banks listed on the Indonesia Stock Exchange in the 2014-2018 period, whereas based on the ratio of NPL, ROA, ROE, NIM, BOPO there were differences in Health Level . Conventional Commercial Banks are in the very healthy category, while Islamic commercial banks are in the less healthy category.